Preparing for the Next Crisis : Establishing a Vulnerability and Shock Monitoring and Response System in Indonesia - World Bank (World Bank, Jakarta, 2013)
Economic and natural crises and shocks are unfortunately recurring events, but the better a country is prepared for such eventualities, the lesser the impact may be. In 2009, in the wake of the global economic crisis, the Government of Indonesia piloted a Crisis Monitoring and Response System (CMRS). The CMRS experience provides valuable inputs for the design of a long-term Vulnerability and Shock Monitoring and Response System (VSMRS). The CMRS covered the whole country, which meant that there was no need for a priori guesses on where crisis impacts might be worst. This report is intended to provide inputs to a discussion within Government of Indonesia agencies, and between the Government and other interested parties (such as donors, international agencies, etc), on what a nascent VSMRS could look like, and how it could operate. It should be stressed that this document does not provide a blueprint for a fully-fledged VSMRS, primarily because such a system could develop in so many ways that much of what would be elaborated in detail might be of little use. The focus is therefore primarylyon discussing general aspects of a VSMRS, to build a common perception on the general direction of such an initiative between the key stakeholders, and to elaborate the concept later on together with a technical working group tasked to do this.